THE ROLE OF GUIDANCE COUNSELING TEACHERS IN DEALING WITH ACTION BULLYING AT MTs PUTRA PUTRA SIMO - Suradji, Muchamad; Tamaji, Sampiril Taurus; Anom, Muharrom Dwiki (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2024)
Research to find out behavior bullying and the role of guidance and counseling teachers in the environment MTS Boys and Girls Simo Lamongan. The research is qualitative in nature to see reality in the field related to bullying and the role of guidance and counseling teachers. Data collection instruments use observation and interview guidelines. Data analysis includes collecting data, reducing data, displaying data, then testing the validity of the data by triangulating the data and then drawing conclusions. Results study this concludes that behavior bullying What has happened at this school is verbal and mental. The role played by guidance and counseling teachers in preventing bullying behavior is to provide guidance and counseling programs implemented in schools by providing classical guidance services, individual counseling services, group counseling services, information services, and also guidance and counseling teachers at MTs Putra Putri Simo this also delivers punishment which educates in order to have a deterrent effect on the perpetrators of the action bullying.